The Effect of a Training Curriculum Using Auxiliary Means in Developing the Skills of Long-Distance Passing and Receiving the Ball (Putting Down) for Al-Tahadi Youth Football Club Players - Mohammed Ashour Abbas (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
The purpose of this paper is to preparing a proposed training curriculum using auxiliary means to develop football passing and putting down skills, identifying the differences between the pre- and post-tests in the skills of passing and putting down football for the experimental and control groups, and identifying the differences in post-tests between the control and experimental groups in the skills of long-distance passing and football putting down. The researcher adopted the experimental method, as the researcher must choose the appropriate method to solve a problem. The research community was chosen by the researcher in an intentional manner, and they were the young football players of the Al-Tahadi Sports Club, the total number of which was (22) players. Since the number was limited, they were chosen as a sample for the research by 100%, as they were divided into a reconnaissance sample, numbering (2). One player, and into two groups: a control group and an experimental group. The number of each group is (10) players after conducting a process of homogeneity and equality among them. One of the most important results reached by the researcher is that: There are statistically significant differences between the pre- and post-tests and for the control and experimental groups in the skills of long-distance passing and putting down, in favor of the post-tests, and there are statistically significant differences in the post-tests between the control and experimental groups in the skills of long-distance passing and putting down, in favor of the post-tests of the experimental group.